Equilibrium, kinetic and thermodynamic study of cesium adsorption onto nanocrystalline mordenite from high-salt solution. (May 2016) - Lee, Keun-Young; Park, Minsung; Kim, Jimin; Oh, Maengkyo; Lee, Eil-Hee; Kim, Kwang-Wook; Chung, Dong-Yong; Moon, Jei-Kwon
Abstract: In this study, the equilibrium, kinetics and thermodynamics of cesium adsorption by nanocrystalline mordenite were investigated under cesium contamination with high-salt solution, simulating the case of an operation and decommissioning of nuclear facilities or an accident during the processes. The adsorption rate constants were determined using a pseudo second-order kinetic model. The kinetic results strongly demonstrated that the cesium adsorption rate of nano mordenite is extremely fast, even in a high-salt solution, and much faster than that of micro mordenite. In the equilibrium study, the Langmuir isotherm model fit the cesium adsorption data of nano mordenite better than the Freundlich model, which suggests that cesium adsorption onto nano mordenite is a monolayer homogeneous adsorption process. The obtained thermodynamic parameters indicated that the adsorption involved a very stable chemical reaction. In particular, the combination of rapid particle dispersion and rapid cesium adsorption of the nano mordenite in the solution resulted in a rapid and effective process for cesium removal without stirring, which may offer great advantages for low energy consumption and simple operation. Highlights: We have investigated the equilibrium, kinetic and thermodynamic properties of Cs adsorption by nano mordenite. The nano mordenite showed a fast adsorption rate and stable binding site for Cs even in high-salt solution. The nano mordenite can be successfully applied to the static adsorption condition.